(untitled) (Research, Society and Development, 2020)
This work consists of an experience report on the use of a teaching project as a learning strategy in Chemistry during Emergency Remote Teaching (ERE), which aimed to motivate and awaken students’ interest in Science through the use of Methodologies Active, in which the student is the protagonist in the educational process. Therefore, the students of the first years of the technical courses of Computer Networks, Electrotechnics and Mechatronics, integrated in CEFET - Nepomuceno Unit participated in a proposal in which they should contextualize the said discipline at home, taking into account the recommendations of social isolation recommended by the Ministry of Health and the World Health Organization (WHO) in 2020. The activities developed by students should be linked to one of the following categories: Recipes at home, Fact or Fake?, Creativity in Focus or Experimenting at Home. The teacher of the discipline was responsible for carefully evaluating the work, and she was also responsible for making the necessary corrections in order to contribute to the training process in the discipline. At the end, the students answered a survey to qualitatively assess their perceptions regarding the work developed during the first two months. It was observed that the strategy used contributed significantly to strengthen the relationship between students and teachers in times of pandemic, in addition to allowing the context of the content developed.